El dumping: como práctica competitiva desleal entre las empresas. - Vera Soto, Mike Anthony (My University, 2018)
The unfair competition nowadays has marked a number of conflicts between the countries, since many of them have been in need of protecting the national production before the situations of dumping that is basically selling the products abroad at a lower price that is given to the domestic market, basically because there are low prices for importers is beneficial, however when the company that makes exports eliminates its competition, it raises prices and produces a monopolized product, adding that the importing country loses an industry that manufactured the product that was also imported, and produced employment, development and economy for the country, is when they appear antidumping reactions that are issued by the National Organization of Commerce that establishes the regulations ordered and consistent and in turn that implements those mechanisms to counteract the negative effects or results, it should be noted that the WTO does not regulate anticompetitive actions but rather that entrepreneurs do, but is in charge of granting tools so that later on States can deal with situations, in this context the following case study is aimed at analyzing unfair competition (dumping) and the effect it brings to companies, whose methodology is based on a qualitative approach based mainly on documented information, with the final results that unfair competitive practices affect not only companies (national production) but largely unbalance the economy of the country that has been a victim.
Las competencias desleales hoy en día han marcado un sin número de conflictos entre los países, ya que muchos de ellos se han visto en la necesidad de proteger la producción nacional antes las situaciones de dumping que es básicamente vender los productos al exterior a un precio menor del que se da al mercado doméstico, básicamente al existir precios bajos para los importadores es beneficioso, sin embargo cuando la empresa que realiza las exportaciones elimina a su competencia eleva los precios y se produce un producto monopolizado, sumando a ello que el país importador pierde una industria la que fabricaba dicho producto del que también se importaba, y producía empleo, desarrollo y economía para el país, es cuando aparecen las reacciones de antidumping que son emitidas por la Organización Nacional del Comercio que establece las normativas ordenadas y coherentes y a su vez que implementa aquellos mecanismos para contrarrestar los efecto o resultados negativos, cabe destacar que la OMC no regula las acciones anticompetitivas sino que realizan los empresarios, sino que es el encargado de otorgar herramientas para que posteriormente sean los Estados los que puedan enfrenar las situaciones, bajo este contexto el siguiente caso de estudio tiene como objetivo analizar la competencia desleal (dumping) en las empresas, cuya metodología es de enfoque cualitativo basándose principalmente de información documentada , teniendo como resultados finales que la practicas competitivas desleales afectan no solo a las empresas sino que en gran parte desequilibra la economía del país que ha sido víctima.
Keywords: COMPETENCIA DESLEAL; COMERCIO; ECONOMÍA